Pengaruh Latihan Shuttle Run terhadap Hasil Tendangan Karate Siswa di SMP Swasta Primbanana Medan Tahun 2023 - Rafika Ardilla; Ricky Hutasoit (CV. Ulil Albab Corp, 2023)
This study aims to determine the effect of shuttle run exercises on karate mawasi kicks on extracurricular activities of SMP Swasta Primbanan. The research method used is experimental quasy with pretest-posttes one group design design. The population in this study are students who follow karate, the sample in this study amounted to 30 people. The research instrument used was a mawasi kick test. Treatment in this research is the exercise of shuttle run given for 6 weeks with frequency of exercise for a week 3 times. The effectiveness test using experimental method with the result of